Development Strategy Of Nature Tourism Object In Sanrobengi Island Boddia Village Galesong District Takalar Regency - Nurhidayah, Nurhidayah; Maddatuang, Maddatuang; Baharuddin, Ichsan Invanni (UNM Geographic Journal, 2017)
This study aims: 1) to know the aspects that can be developed as a natural tourist attraction in Sanrobengi Island. 2) to know the public perception of the development of natural attractions in Sanrobengi Island. 3) to know the prospect of developing natural attractions in Sanrobengi Island. Objects in this study are tourists and the public. The data presented in the form of primary data taken from the questionnaire "Prospect of Sanrobengi Island Tourism Object Development in Boddia Village Galesong District Takalar District". Informant retrieval was taken using accidental sampling technique and purposive sampling technique. Data analysis used is qualitative descriptive analysis and SWOT analysis.The results show that the appropriate development strategy in the development of Sanrobengi Island as a natural tourist attraction is a strategy of Strength - Opportunities. The conclusions obtained include: physical aspect and social aspects strongly support the development of Sanrobengi Takalar Island as a natural tourist attraction. Public and tourist perceptions of natural attractions that agree to do more development. The development strategy that can be done include developing interest tourism, enhancing cooperation between central and local government, making promotion through website, banner, and billboards, local people's role in developing tourist object such as boat service utilization as well as maintaining and maintaining coral reef habitat environment.